Analytical Solution for Waves Propagation in Heterogeneous Acoustic/Porous Media Part II: The 3D Case (Communications in Computational Physics, 2010)
We are interested in the modeling of wave propagation in an infinite bilayeredacoustic/poroelastic media. We consider the biphasic Biot's model in the poroelasticlayer. The first part was devoted to the calculation of analytical solution in twodimensions, thanks to Cagniard de Hoop method. In the first part (Diaz and Ezziani,Commun. Comput. Phys., Vol. 7, pp. 171-194) solution to the two-dimensional problemis considered. In this second part we consider the 3D case.